Genome-wide approaches for the identification of markers and genes associated with sugarcane yellow leaf virus resistance - Pimenta, Ricardo José Gonzaga; Aono, Alexandre Hild; Burbano, Roberto Carlos Villavicencio; Coutinho, Alisson Esdras [UNESP]; da Silva, Carla Cristina; dos Anjos, Ivan Antônio; Perecin, Dilermando [UNESP]; Landell, Marcos Guimarães de Andrade; Gonçalves, Marcos Cesar; Pinto, Luciana Rossini; de Souza, Anete Pereira (My University, 2021)
Sugarcane yellow leaf (SCYL), caused by the sugarcane yellow leaf virus (SCYLV) is a major disease affecting sugarcane, a leading sugar and energy crop. Despite damages caused by SCYLV, the genetic base of resistance to this virus remains largely unknown. Several methodologies have arisen to identify molecular markers associated with SCYLV resistance, which are crucial for marker-assisted selection and understanding response mechanisms to this virus. We investigated the genetic base of SCYLV resistance using dominant and codominant markers and genotypes of interest for sugarcane breeding. A sugarcane panel inoculated with SCYLV was analyzed for SCYL symptoms, and viral titer was estimated by RT-qPCR. This panel was genotyped with 662 dominant markers and 70,888 SNPs and indels with allele proportion information. We used polyploid-adapted genome-wide association analyses and machine-learning algorithms coupled with feature selection methods to establish marker-trait associations. While each approach identified unique marker sets associated with phenotypes, convergences were observed between them and demonstrated their complementarity. Lastly, we annotated these markers, identifying genes encoding emblematic participants in virus resistance mechanisms and previously unreported candidates involved in viral responses. Our approach could accelerate sugarcane breeding targeting SCYLV resistance and facilitate studies on biological processes leading to this trait.